Sonoelectrochemical detection of copper within industrial effluent: A critical assessment - Davis, J; Cardosi, M; Brown, I; Hetheridge, M; Compton, R (2001)
The utility of combining an ultrasound probe with conventional electrochemical stripping methodology has been assessed for the mercury free determination of copper within industrial effluent. The introduction of an ultrasound field within the cell during the accumulation stage is shown to significantly enhance the sensitivity of the technique. Two compositionally distinct samples were assessed and the results compared with those obtained from in house and independent analysis (ICP). A brief review of the electroanalytical alternatives to mercury electrodes with regard to copper determination has been included and the various merits and limits of the sonoelectrochemical approach compared and appraised.